Problem-Based Learning vs Inquiry Learning: Strategies to Improve Students' Sociological Literacy and Critical Thinking Skills - Hawa, Esa El; Wilodati, Wilodati; Komariah, Siti (Jurnal Pendidikan Progresif, 2025)
Problem-Based Learning vs Inquiry Learning: Strategies to Improve Students' Sociological Literacy and Critical Thinking Skills. Objective: This study aims to analyze the comparative effectiveness of the Problem-Based Learning (PBL) and Inquiry Learning (IL) models in improving the Sociological Literacy and Critical Thinking Skills of high school students, as well as to explore the significant contribution of the comparison of these two models to the sociological pedagogical literature in the 21st century. Methods: This study used a quasi-experimental design with a quantitative approach, involving two randomly selected treatment groups from grade XI students. The total number of research participants was 72 students. The main instruments used were pretest and posttest measures of Sociology Literacy (30 multiple-choice questions) and Critical Thinking Skills (7 essay questions). Inferential data analysis was carried out using Covariance Analysis (ANCOVA) with pretest scores as covariates. The use of ANCOVA is essential to statistically control differences in students' initial abilities and validate the pure impact of the learning model. Findings:  The results showed that the PBL Model was significantly more effective (p < 0.05) in improving Sociological Literacy and Critical Thinking Skills compared to the IL Model. This advantage was confirmed by the substantially higher adjusted average (Adjusted Marginal Means) in the PBL group for both outcome variables. Conceptually, these findings show a superior fit between the directional problem-solving framework in PBL and the demands of complex sociological reasoning. Conclusion: Problem-Based Learning is the most effective instructional strategy for cultivating analytical skills and critical thinking in the context of Sociology. The PBL model is successful because its directional scaffolding structure and cognitive conflict are more effective in training critical sub-skills such as contextual analysis and evidence-based decision-making. This study recommends the sustainable adoption of PBL by Sociology teachers to foster robust learning that aligns with the demands of global socio-analytical competencies. Keywords: problem-based learning, inquiry learning, sociological literacy, critical thinking, 21st century.